SPECT imaging of fibrin using fibrin‐binding peptides. (11th January 2013) - Starmans, Lucas W. E.; van Duijnhoven, Sander M. J.; Rossin, Raffaella; Aime, Silvio; Daemen, Mat J. A. P.; Nicolay, Klaas; Grüll, Holger
Abstract : Noninvasive detection of fibrin in vivo using diagnostic imaging modalities may improve clinical decision‐making on possible therapeutic options in atherosclerosis, cancer and thrombus‐related pathologies such as pulmonary embolism and deep venous thrombosis. The aim of this study was to assess the potential of a novel 111 In‐labeled fibrin‐binding peptide (FibPep) to visualize thrombi in mice noninvasively using single‐photon emission computed tomography (SPECT). FibPep and a negative control peptide (NCFibPep) were synthesized and their fibrin‐binding properties were assessed in vitro . FibPep showed enhanced binding compared with NCFibPep to both fibrin and blood clots. FibPep bound to fibrin with a dissociation constant ( K d ) of 0.8 μm, whereas NCFibPep displayed at least a 100‐fold lower affinity towards fibrin. A FeCl3 ‐injury carotid artery thrombosis mouse model was used to evaluate the peptides in vivo . FibPep and NCFibPep displayed rapid blood clearance and were eliminated via the renal pathway. In vivo SPECT imaging using FibPep allowed clear visualization of thrombi. Ex vivo biodistribution showed significantly increased uptake of FibPep in the thrombus‐containing carotid in comparison to the noninjured carotid (5.7 ± 0.7 and 0.6 ± 0.4% injected dose per gram (%ID g −1 ), respectively; p < 0.01; n = 4), whereas nonspecific NCFibPep did not (0.4 ± 0.2 and 0.3 ± 0.0%ID g −1, respectively; n = 4). In conclusion, FibPep displayed high affinity towards fibrin in vitro and rapid blood clearance in vivo, and allowed sensitive detection of thrombi using SPECT imaging. Therefore, this particular imaging approach may provide a new tool to diagnose and monitor diseases such as atherosclerosis and cancer. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : In this study, we show the potential of a novel 111 In‐labeled fibrin‐binding peptide (FibPep) for noninvasive detection of fibrin deposition using SPECT. FibPep and a negative control peptide (NCFibPep) were synthesized and their fibrin‐binding properties were assessed in vitro and in vivo . In vivo SPECT imaging using FibPep allowed clear visualization of thrombi. Ex vivo biodistribution showed significantly increased uptake of FibPep in the thrombus‐containing carotid in comparison to the noninjured carotid, whereas nonspecific NCFibPep did not.